Loiasis in sub-Saharan migrants living in Spain with emphasis of cases from Equatorial Guinea - Sabino Puente; German Ramírez-Olivencia; Mar Lago; Mercedes Subirats; Francisco Bru; Eugenio Pérez-Blazquez; Marta Arsuaga; Concepción Ladron de Guevara; Fernando de la Calle-Prieto; Belén Vicente; Montserrat Alonso-Sardón; Moncef Belhassen-Garcia; et al. (BMC, 2020)
Abstract Background Loiasis is an uncommon and poorly understood parasitic disease outside endemic areas of Africa. The aim of this study was to describe the clinical and biological patterns and treatment of imported loiasis by sub-Saharan migrants diagnosed in Madrid, Spain. Methods A retrospective study was conducted with sub-Saharan immigrants seen at the Tropical Medicine Unit of the Carlos III Hospital in Madrid, Spain, a reference center, over 19 years. Categorical variables were expressed as frequency counts and percentages. Continuous variables were expressed as the mean and standard deviation (SD) or median and interquartile range (IQR: Q3-Q1). Chi-square tests were used to assess the association between categorical variables. The measured outcomes were expressed as the odds ratio (OR) with a 95% confidential interval. Continuous variables were compared by Student's t-tests or Mann-Whitney U tests. Binary logistic regression models were used. P <  0.05 was considered a statistically significant difference. Results One hundred thirty-one migrants from tropical and subtropical areas with loiasis were identified. Forty-nine patients were male (37.4%). The migrants' mean age (±SD) was 42.3 ± 17.3 years, and 124 (94.7%) were from Equatorial Guinea. The median time (IQR) between arrival in Spain and the first consultation was 2 (1-7) months. One hundred fifteen migrants had eosinophilia, and one hundred thirteen had hyper-IgE syndrome. Fifty-seven patients had pruritus (43.5%), and thirty patients had Calabar swelling (22.9%). Seventy-three patients had coinfections with other filarial nematodes (54.2%), and 58 migrants had only Loa loa infections (45.8%). One hundred two patients (77.9%) were treated; 45.1% (46/102) patients were treated with one drug, and 54.9% (56/102) patients were treated with combined therapy. Adverse reactions were described in 14 (10.7%) migrants. Conclusions Our patients presented early clinical manifestations and few atypical features. Thus, physicians should systematically consider loiasis in migrants with a typical presentation. However, considering that 72.5% of the patients had only positive microfilaremia without any symptoms, we suggest searching for microfilaremia in every migrant from endemic countries for loiasis presenting with eosinophilia.